Nilda - Mohr, Nicholasa (Houston, Tex. : Piñata Books, 2011)
A young girl growing up in Spanish Harlem in the 1940's watches the secure world of her childhood years slowly erode away.
4.5
5-8.
5-8
Keywords: Puerto Ricans -- New York (N.Y.) -- Juvenile fiction; Puerto Ricans -- New York (N.Y.) -- Fiction; Puerto Ricans -- Fiction; Teacher's guide; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction